Intra‐hospital dissemination of clinical and environmental isolates of Stenotrophomonas maltophilia from Tehran. (22nd November 2020) - Kardan‐Yamchi, J.; Hajihasani, A.; Talebi, M.; Khodaparast, S.; Azimi, A.; Rahbar, M.; Fallah, F.; Douraghi, M.
Abstract: Stenotrophomonas maltophilia isolates are responsible for various hospital‐acquired infections and are particularly increasing in the immunocompromised patients. The aim of this study was to determine the clonal relatedness between S. maltophilia isolates originating from the clinic and environment. A total of 150 S. maltophilia isolates from patients and 1108 environmental samples obtained in three hospitals from Tehran. Following molecular identification targeting 23S rRNA gene, the clonal relatedness of the environmental and clinical isolates was determined using pulsed field gel electrophoresis (PFGE). Of the 150 clinical and 18 environmental isolates identified using phenotypic tests, the speciation of 120 and 15 was confirmed by targeting the 23S rRNA gene. The 24 common pulsotypes (PTs) and 32 single PTs were identified by PFGE. Only a small cluster was shared among the clinic and environment within a hospital; therefore, the intra‐hospital dissemination of certain isolates of S. maltophilia among the clinic and environment was demonstrated. Abstract : Significance and Impact of the Study: A wide genetic diversity of S. maltophilia strains from the clinical and environmental sources was found. The small clusters of common pulsotypes (PTs) in the clinical settings were identified which indicates the existence of a common source for S. maltophilia to disseminate between different wards. The transmission of S. maltophilia among the environment and the patients within a hospital was confirmed by the shared genotypes among the environmental and clinical isolates. These data can alert the infection control committee to monitor the factors involved in dissemination of nosocomial pathogens.